Developing an on-campus creative economy clinic to elevate the quality of existing community service program - Zainal, Andri; Farza, T. Citra Nisa; Harahap, Khairunnisa; Dwi Putra, Pasca (ASEAN Journal of Community Engagement, 2020)
The ongoing community service program has not provided optimal and sustainable outcomes that can improve the creative economy sector as a partner, especially in the era of technological disruption. This study describes the importance of setting up a creative economy clinic at the university, which is based on the needs of upscaling local micro, small, and medium enterprises (MSMEs’) performance. The discussions presented in the paper arise from a qualitative conceptual study using an instrumental case study approach, linking insights from theoretical perspectives and works across disciplines that concern the development of a creative economy clinic. The results of the discussion highlight the potential outcomes of establishing an on-campus creative economy clinic, ensuring the business sustainability of MSMEs in the era of disruptive technology. An initial assessment related to the needs of MSMEs is required as a strategic step in the development of the ecosystem of related creative economy clinics using each university’s competitive advantage.